2008
DOI: 10.1007/s11661-008-9582-6
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Geometry and Through-Thickness Strain Gradients in Asymmetric Rolling

Abstract: Experiments and simulations focusing on cold rolling under conditions where the work roll velocities are different (asymmetric rolling) have been performed to provide a basic framework for understanding the effects of the roll velocity ratio and deformation geometry on through thickness shear strain development. It is shown that deformation geometry, controlled by varying the reduction per pass, has a significant impact on the through thickness shear strain gradients at a given level of asymmetry. Large reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…It is evident that, the strain rises in parabolic course with increase of the R value. This situation should be explained in terms of a presence of additional shear strain, which value is proportional to the roll-speed mismatch [17]. A higher imposed strain by the DSR may be also attributed to an activation of additional slip system 〈1 1 0〉 {1 0 0} resulting from an increase of the strain rate [18], which linearly rises with the R value (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is evident that, the strain rises in parabolic course with increase of the R value. This situation should be explained in terms of a presence of additional shear strain, which value is proportional to the roll-speed mismatch [17]. A higher imposed strain by the DSR may be also attributed to an activation of additional slip system 〈1 1 0〉 {1 0 0} resulting from an increase of the strain rate [18], which linearly rises with the R value (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Plots of a calculated accumulated strain (a) and strain rate (b)[17] and measured microhardness change ((c)-after 2 rolling passes) as a function of the rolls velocity ratio R. (d) Tensile curves obtained for sample in the initial state and after 2 rolling passes with different values of the R (TYS-tensile yield strength, UTS-ultimate tensile strength).…”
mentioning
confidence: 99%
“…The HL structure was produced by asymmetric rolling (13,14) and subsequent partial recrystallization (see Materials and Methods for details). The asymmetric rolling elongated the initial equiaxed grains (Fig.…”
Section: Microstructure Of Heterogeneous Lamella Structurementioning
confidence: 99%
“…Therefore, the high angle grain boundaries in the samples for RUDV of 1.1 should result in its lower ductility compared with that for RUDV of 1.4. Roumina et al15 also found that the Al alloy strips exhibit high formability when they are produced via the shear deformation.…”
Section: Discussionmentioning
confidence: 97%